Retrofitting of bridge hollow piers with CFRP - Pedro Delgado (2007)
Hollow bridge piers generally have large section dimensions, with reinforcement bars spread along both wall faces. Unlike common solid section columns, quite often the shear effect has great importance on the pier behavior. Therefore, it is of particular relevance that special attention is given to this issue when the assessment and retrofit of RC hollow section piers is envisaged. Representative of typical bridge construction, RC piers were tested at LESE the Laboratory of Earthquake and Structural Engineering of the Faculty of Engineering of University of Porto. Experimental tests of hollow section piers with square and rectangular cross sections under cyclic loading are being carried out in order to compare the results of the original piers and CFRP retrofitted piers, regarding benefits on their structural behavior and comparing the results with analytical predictions. The adopted numerical methodologies are based on finite element analysis using 3D elements with a Continuum Damage Mechanics model for the concrete under tensile and compressive reversals and truss elements with the Menegotto-Pinto model for the cyclic behavior of steel reinforcement. For different rectangular cross sections, the interaction between pier walls is likely to affect their global behavior and damage. The main purpose of this paper is therefore to present several strategies of retrofit with CFRP in order to prevent shear or flexural collapse mechanisms, or both. Different amounts of strip layers were applied for shear retrofit and jacket confinement near the pier base section was adopted for increasing ductility. It is intended to assess the structural behavior and safety improvement due to the adoption of different CFRP retrofit techniques and to illustrate the external and internal damage pattern. The need of interior retrofit is discussed on the basis of experimental evidence from some of the tests; therefore a strategy of internal confinement is also presented in order to prevent interior concrete spalling and longitudinal rebar buckling.